2007
DOI: 10.3917/cips.073.0061
|View full text |Cite
|
Sign up to set email alerts
|

Harcèlement moral au travail, survictimation et problèmes du harceleur : quand les victimes sont jugées aussi responsables que leurs harceleurs

Abstract: Résumé Trente-deux scénarios relatifs au harcèlement professionnel variant en fonction des explications causales et de la survictimation du harcelé, des problèmes psychologiques du harceleur et de la situation économique de l’entreprise ont été soumis à soixante-quatre sujets qui jugeaient l’équité de la situation, la responsabilité du harcelé et du harceleur et la probabilité de venir en aide. Les résultats indiquent que le harcèlement est jugé d’autant moins équitable mais le harcelé, d’autant plus responsab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
9
1
2
Order By: Relevance
“…As previous results have shown (Desrumaux, 2007;Desrumaux & de Chacus, 2007), the fact of knowing that somebody is revictimized decreases the intention to assist. This appears paradoxical, because we might think that a revictimized person needs more help than others.…”
Section: Deviant and Prosocial Employees' Behaviors And Their Consequmentioning
confidence: 64%
See 3 more Smart Citations
“…As previous results have shown (Desrumaux, 2007;Desrumaux & de Chacus, 2007), the fact of knowing that somebody is revictimized decreases the intention to assist. This appears paradoxical, because we might think that a revictimized person needs more help than others.…”
Section: Deviant and Prosocial Employees' Behaviors And Their Consequmentioning
confidence: 64%
“…Thus, harassment is judged more equitable when the climate is based on strict rules and procedures (Desrumaux-Zagrodnicki et al, 2004). Another study shows that the bullied person is considered more responsible if he or she has already been victimized and when he or she offers internal explanations (Desrumaux, 2007). These judgments can be a clue, a way to explain the solitude and lack of help giving.…”
Section: Research On Workplace Bullyingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, harassment is judged more equitable when the climate is based on strict rules and procedures (Desrumaux-Zagrodnicki et al, 2004). Second, it has been found that the bullied is considered more responsible if he or she has already been victimized and when he or she evokes internal explanations (Desrumaux, 2007). Third, revictimization decreases the intent to help.…”
Section: Research On Workplace Bullyingmentioning
confidence: 99%